Prevalence, Bacterial Isolation, and Antimicrobial Susceptibility of Clinical Mastitis in Lactating Camels in Southern Algeria (Illizi and Oued Souf) - Djeddi, Khaled; Hind, Houssou; Gouasmia, Yassine (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Clinical mastitis in she-camels (Camelus dromedarius) is a significant concern for camel farming, particularly in regions such as Oued Souf and Illizi provinces in Algeria. Mastitis affects the health of the animals and the quality of milk, impacting productivity and herd management. Understanding the prevalence, bacteriological characteristics, and risk factors associated with mastitis is critical for developing effective management strategies. Objective: This study aims to investigate the prevalence, risk factors, and bacteriological characteristics of clinical mastitis in Sahraoui she-camels in the Oued Souf and Illizi regions of Algeria, with a focus on antimicrobial susceptibility patterns of the pathogens involved. Methods: A total of 170 multiparous Sahraoui she-camels were clinically examined. Milk samples were collected from affected animals, and bacterial isolates were obtained and identified. Antimicrobial susceptibility testing was performed on the isolates to determine resistance patterns. Risk factors, such as tick infestation, udder lesions, and the use of anti-suckling devices, were also assessed. Results: Gram-positive cocci were the predominant pathogens, with Streptococcus agalactiae accounting for 85% of bacterial isolates. The antimicrobial susceptibility testing revealed that oxytetracycline, doxycycline, erythromycin, and cotrimoxazole showed 100% efficacy. Sulfamethazine/trimethoprim and tylosin exhibited 85% susceptibility, while penicillin and amoxicillin were effective in 60% of cases. Enrofloxacin demonstrated moderate efficacy, with a 50% susceptibility rate. The study also identified key risk factors such as tick infestation, udder lesions, and anti-suckling devices. Conclusions: The study underscores the importance of monitoring bacterial resistance in camel mastitis and suggests that appropriate treatment strategies, including the use of oxytetracycline, doxycycline, and erythromycin, should be prioritized. Effective management of mastitis in Algerian camel herds requires addressing the identified risk factors, such as tick infestations and udder injuries, and implementing appropriate prevention and treatment strategies to improve animal health and milk quality.